Assessment of Surface Roughness in Milling of Wood with Different Material Temperature and Cutting Parameters - Mustafa Korkmaz; Mehmet Budakçı; Izham Kılınç (BioResources, 2024)
Effects of wood temperature were studied during CNC router processing relative to the resulting surface roughness, addressing a considerable gap in wood machining research. Three wood species (Scots pine, beech, and poplar) were machined at four temperatures (-20 °C, 0 °C, 20 °C, and 50 °C) to simulate diverse climatic conditions. The experiments were conducted at varied spindle speeds (6000, 12000, and 18000 rpm) and feed rates (3000 and 6000 mm/min). Surface roughness was measured using a portable tester in accordance with relevant ISO standards. A full factorial design was used to evaluate the effects of wood species, temperature, spindle speed, and feed rate on surface roughness. Results revealed a strong correlation between processing temperature and surface roughness, with a 25.9% increase in roughness observed as temperature rose from -20 °C to 50 °C. This temperature effect was consistent across all wood species, though its magnitude varied. The study also found that wood type, spindle speed, and feed rate significantly influenced surface quality, interacting with temperature effects. These findings suggest that controlling wood temperature during processing could be crucial for maintaining consistent surface quality in industrial applications, especially in facilities operating under variable environmental conditions.